(untitled) (Research, Society and Development, 2022)
Memory difficulties influence the learning process, since the ability to evoke knowledge over time and apply it is a necessity for students. Brazil had the worst scores in working memory and short-term memory compared to other children from countries such as Italy, England, Argentina and Canada. In this sense, this research aimed to assess how this topic has been researched in Brazil by means of a survey of the works produced by postgraduate programs between 2011 and 2021 and which were catalogued in the database of the Brazilian Digital Library of Theses and Dissertations. This is a state-of-the-art research, of a bibliographic and documentary nature and has a descriptive character. After reading and analyzing the abstracts, 12 studies were selected, being 2 theses and 10 dissertations, highlighting 2011 and 2016 as the years with the highest scientific production, 5 papers total (41.7%). Regarding location, the Southeast of Brazil (58.3%) was predominant, followed by the South (25%) and Northeast (16.7%). Eight (8) of these papers (66.7%) addressed difficulties related to working memory, and among the learning difficulties are reading and comprehension, dyslexia, Attention Deficit Disorder and dyscalculia and difficulty in mathematics, totaling 8 (66.7%). The overall analysis pointed to the importance of memory for understanding learning difficulties, yet in these 10 years few studies were found that dealt with the subject, which shows the need for furthering research, as well as its association with neurosciences so as to trace strategies which may help devise pedagogical plans to meet special educational needs.